2012
DOI: 10.1093/cid/cir989
|View full text |Cite
|
Sign up to set email alerts
|

Does an Index Composed of Clinical Data Reflect Effects of Inflammation, Coagulation, and Monocyte Activation on Mortality Among Those Aging With HIV?

Abstract: Among HIV-infected individuals, independent of CD4, HIV-1 RNA, and age, hemoglobin and markers of liver and renal injury are associated with inflammation. Addition of D-dimer and sCD14, but not IL-6, improves the predictive accuracy of the VACS Index for mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
187
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(197 citation statements)
references
References 28 publications
7
187
1
Order By: Relevance
“…40 This improved predictive value based on measures of clinical end points associated with inflammation (anemia, liver injury, kidney injury) supports a central role for inflammation in disease progression caused by HIV. 38 In the case of anemia, what is particularly striking is that when analyzing the factors that make up the VACS index, anemia was not only correlated with other markers of inflammation, but was also found to be an independent prognostic factor for mortality. 41 When serum levels of sCD14, IL-6, and D-dimer were evaluated in the VACS cohort and included in mortality predictions, D-dimer and sCD14 further improved predictive accuracy.…”
Section: Hiv and Aging: The Inflammatory Connectionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 This improved predictive value based on measures of clinical end points associated with inflammation (anemia, liver injury, kidney injury) supports a central role for inflammation in disease progression caused by HIV. 38 In the case of anemia, what is particularly striking is that when analyzing the factors that make up the VACS index, anemia was not only correlated with other markers of inflammation, but was also found to be an independent prognostic factor for mortality. 41 When serum levels of sCD14, IL-6, and D-dimer were evaluated in the VACS cohort and included in mortality predictions, D-dimer and sCD14 further improved predictive accuracy.…”
Section: Hiv and Aging: The Inflammatory Connectionmentioning
confidence: 99%
“…The VACS is a well-described patient cohort of 1302 HIV ϩ patients on cART with age/race/site-matched HIV Ϫ controls on whom blood and DNA specimens have been banked. 38 This patient cohort has been used to develop the VACS index, an evaluation of 7 variables (age, CD4 count, HIV-1 status, hemoglobin, FIB-4 index, hepatitis C infection, and eGFR) used to help predict mortality. 39 The VACS index is more predictive of mortality than the Restricted Index, which only considers age, CD4 count, and HIV-1 status.…”
Section: Hiv and Aging: The Inflammatory Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is calculated using the patient's age, CD4 cell count, HIV ribonucleic acid and hemoglobin levels, renal and hepatic function, and hepatitis C virus serostatus. 26,27 The VACS Index Score ranges from 0 to 164 points, with higher scores indicating greater burden of disease and higher risk of morbidity and mortality (each additional five points indicates approximately a 20% increased risk of five-year mortality). 27,28 We calculated body mass index (BMI) based on weight and height as recorded in the electronic medical record during routine clinical care.…”
Section: Measurementsmentioning
confidence: 99%
“…5 It has also been shown to predict morbidity, including hospitalizations and medical intensive care unit admissions, 6 and correlate with HIV-related chronic inflammation. 7 Because frailty and the VACS Index predict the same outcomes, the VACS Index has been used in two recent studies as a surrogate marker to identify frail HIVinfected persons. 8,9 Another study has also shown that the median VACS Index scores of frail HIV-infected persons were significantly higher compared to nonfrail individuals.…”
mentioning
confidence: 99%